2020
DOI: 10.1093/aobpla/plaa032
|View full text |Cite
|
Sign up to set email alerts
|

Direct fluorescence imaging of lignocellulosic and suberized cell walls in roots and stems

Abstract: Background and Aims Investigating plant structure is fundamental in botanical science and provides crucial knowledge for the theories of plant evolution, ecophysiology, and for the biotechnological practices. Modern plant anatomy often targets the formation, localization and characterization of cellulosic, lignified, or suberized cell walls. While classical methods developed in the 60s are still popular, recent innovations in tissue preparation, fluorescence staining, and microscopy equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 177 publications
2
43
0
1
Order By: Relevance
“…Some authors reported that polysaccharides were compounds without autofluorescence [16,31] . However, with other stains such as Congo red, cellulose could fluoresce between 570–620 nm; [14,32] for holocellulose, Donaldson et al [33] . detected its fluorescence emission in red tones at 600 nm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported that polysaccharides were compounds without autofluorescence [16,31] . However, with other stains such as Congo red, cellulose could fluoresce between 570–620 nm; [14,32] for holocellulose, Donaldson et al [33] . detected its fluorescence emission in red tones at 600 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure for preparing plant tissue samples for analysis with epifluorescence microscopy is in Supporting Information , Methods S1. The fixation technique was based on Ruzin [54] with modifications based on Kitin et al [14] . The procedure to stain the samples was based in Loza‐Cornejo and Terrazas [55] .…”
Section: Methodsmentioning
confidence: 99%
“…This could be due to the presence of perforation plates (Brodersen et al, 2018;Shane et al, 2000) or persistent xylem cross-walls (Sanderson et al, 1988). In this study, we did not divide 81-37-8) and PEG 400 (PEG 400:glycerol:water = 10:9:1, v:v) allow intense staining of lipids and suberin lamellae (Kitin et al, 2020). We also assume that xylem sap has the same viscosity as water.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the CLSM were consistent with previous studies. Kitin et al (2020) also reported the fluorescence of lignin and suberin in plant cells under CLSM. Heinämäki et al (2017) confirmed the melting behavior of suberin monomers.…”
Section: Sms Distribution In the Specimensmentioning
confidence: 98%
“…Suberin and lignin are naturally fluorescent substances in plant cells for its pheno-lic structure (Hutzler et al 1998, Kitin et al 2020. The microscopic distribution of SMs in specimens was detected by a Leica TCS SP8 confocal microscope (Leica Microsystems Inc., Wetzlar, Germany) with a krypton/argon laser emitting at wavelengths of 488 nm.…”
Section: Confocal Laser Scanning Microscopy Analysismentioning
confidence: 99%